2012
DOI: 10.1371/journal.pone.0030025
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Infection in India: Results of a Prospective Hospital Based Multi-Centric Study

Abstract: BackgroundChikungunya (CHIKV) has recently seen a re-emergence in India with high morbidity. However, the epidemiology and disease burden remain largely undetermined. A prospective multi-centric study was conducted to evaluate clinical, epidemiological and virological features of chikugunya infection in patients with acute febrile illness from various geographical regions of India.Methods and FindingsA total of 540 patients with fever of up to 7days duration were enrolled at Karnataka Institute of Medical Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
65
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 31 publications
12
65
3
Order By: Relevance
“…[22][23][24] Though the guidelines say that diarrhea and vomiting are more common in children but this study revealed that a good number of adult patients had these symptoms as well which we can find in other study also. 25,26 In this study lymphopenia was more frequent that is about 91% and thrombocytopenia was less and that is 43%. This is similar with other study where lymphopenia was 87% and thrombocytopenia was 37%.…”
Section: Discussionsupporting
confidence: 45%
“…[22][23][24] Though the guidelines say that diarrhea and vomiting are more common in children but this study revealed that a good number of adult patients had these symptoms as well which we can find in other study also. 25,26 In this study lymphopenia was more frequent that is about 91% and thrombocytopenia was less and that is 43%. This is similar with other study where lymphopenia was 87% and thrombocytopenia was 37%.…”
Section: Discussionsupporting
confidence: 45%
“…A particularly large CHIKV outbreak began in eastern Africa in late 2004 and then spread to Indian Ocean islands, India, and southeast Asia over the next 2 years. Estimates suggest that nearly 2 million people became infected during this outbreak (2,(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…CHIKV genomic RNA is detectable at the time of symptom onset and then declines to undetectable levels within 7 days (5,8,11,13,17,23). In contrast, IgM is not uniformly positive until day 5 after illness onset, with IgG appearing 1 to 2 days after IgM (5,8,24,25).…”
mentioning
confidence: 99%
“…A recent prospective cohort study of acute febrile illnesses in children at study sites in several Southeast Asian countries determined that CHIKV infection was responsible for approximately 3-fold higher number of cases compared to dengue viruses [8], although this may be an overestimate due to the limited confirmatory testing performed on anti-CHIKV IgM positive samples. Similar hospital-based studies during 2008-2009 in India identified CHIKV as the cause of almost 50% of acute febrile illnesses in the southern state of Karnataka [9], an area greatly affected by the 2005-2006 epidemics.…”
Section: About the Disease And Pathogenmentioning
confidence: 76%